Is There an Application for Improving Marital Satisfaction? An Overview of Smartphone Usage in Urban Young Adults' Marital Interactions - Rumondor, Pingkan C. B (UI Scholars Hub, 2019)
Technological advancement is like a double-edged sword; that is, it has both positive and negative effects on marital interactions. Although previous studies have discussed the negative impact of excessive smartphone usage on marriage, smartphones, as a means of promoting positive marital interactions, require further investigation. Thus, this descriptive study provides an overview of smartphone usage that supports marital interactions. The participants included 265 married individuals (20-40 years of age) living in the Greater Jakarta area (Jabodetabek), who completed an online survey about smartphone usage in their marital interactions as well as a marital satisfaction assessment. Thematic analyses of the qualitative data were conducted to describe smartphone habits such as the most frequently used applications, the most helpful features in supporting positive marital interactions, and perceived benefits. Correlations and cross-tabulations were also performed to describe the association between marital satisfaction and smartphone usage. The findings indicated that the frequency of smartphone usage did not correlate with marital satisfaction. However, smartphone usage with a spouse served as a tool for relationship maintenance. The results of this study can be helpful for young married adults in urban areas, especially those aiming to maximize smartphone usage in order to improve marital interactions and satisfaction.